Peningkatan Nilai Tambah UMKM Catering Melalui Pelatihan Garnish Pada Produk Tumpeng - Tikasari, Nopi; Arreski, Dwi Fitra; W, Ria Ekanindya; Kamela, Hurian (Universitas Pahlawan Tuanku Tambusai, 2024)
This community service (PkM) activity aims to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the catering sector through training in making garnishes for tumpeng products. Attractive and aesthetic garnishes can add value to tumpeng products, attracting consumer attention and increasing sales. This training was designed using a participatory method, which involved imposing garnish-making techniques, direct practice, and evaluating participants' results. After participating in this activity, it is hoped that the MSME catering participants can apply creative garnishing techniques to their tumpeng products, thereby improving the quality of the product's appearance. Participants are also expected to have a deeper understanding of the importance of product visualization in increasing attractiveness and sales. The expected output from this PkM activity is that there will be an increase in the skills of the assisted MSMEs in making garnishes, an increase in the aesthetic value of tumpeng products, and an increase in product sales volume. Apart from that, this training can contribute to developing the local economy by increasing the competitiveness of MSMEs in the market.